2010
DOI: 10.1371/journal.pone.0014047
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Adhesion-GPCR GPR126 Is Required for Embryonic Development in the Mouse

Abstract: Adhesion-GPCRs provide essential cell-cell and cell-matrix interactions in development, and have been implicated in inherited human diseases like Usher Syndrome and bilateral frontoparietal polymicrogyria. They are the second largest subfamily of seven-transmembrane spanning proteins in vertebrates, but the function of most of these receptors is still not understood. The orphan Adhesion-GPCR GPR126 has recently been shown to play an essential role in the myelination of peripheral nerves in zebrafish. In parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
90
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 33 publications
7
90
0
1
Order By: Relevance
“…These results are concordant with a report that demonstrated that Gpr126 is expressed in endothelial cells, and the expression could be induced by angiogenic factors (29). Severe cardiovascular defects that result in embryonic lethality were observed in the Gpr126 knock-out mouse (28). Waller-Evans et al (28) did find internal hemorrhaging in mutant embryos, although no obvious vasculogenesis defect was identified.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are concordant with a report that demonstrated that Gpr126 is expressed in endothelial cells, and the expression could be induced by angiogenic factors (29). Severe cardiovascular defects that result in embryonic lethality were observed in the Gpr126 knock-out mouse (28). Waller-Evans et al (28) did find internal hemorrhaging in mutant embryos, although no obvious vasculogenesis defect was identified.…”
Section: Discussionsupporting
confidence: 91%
“…GPR126 is a seven-transmembrane receptor that is evolutionarily conserved not only in the protein sequence but also in synteny of the surrounding genomic region in vertebrates (28). Besides the conserved protein sequences, recent studies have reported that GPR126 has conserved physiological functions during peripheral nerve development in fish and mammals (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initiative has revealed that Gpr126, a vertebrate aGPCR essential for the myelination of peripheral nerves by Schwann cells (Monk et al, 2009(Monk et al, , 2011, is required for embryonic viability and cardiovascular development in the mouse (Waller-Evans et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion GPCR are characterized by long extracellular N termini, which are composed of multiple functional domains, a seven-transmembrane spanning (7TM) domain, and a cytoplasmic tail. Adhesion GPCR are believed to play a role in immune functions (3,4), angiogenesis (5), cell polarity (6,7), and development (8,9). Mutations in some members of the protein family were identified as the cause of inherited developmental defects in humans such as Usher syndrome (VLGR1) (10) and bilateral frontoparietal polymicrogyria (GPR56) (11).…”
mentioning
confidence: 99%